Increased Production, Waterglass Roll Saving Dyeing Efficiency, Branding Strategy, and Digital Marketing in Muara Bungo Mulia Batik - Istianingsih, Nanik; Ariyanto M, Ariyanto M; Zulkifli, Zulkifli; Poiran, Poiran; Rianto, Rianto (Pascasarjana Universitas Mataram, 2024)
Batik is a cultural heritage of the Indonesian nation that has been recognized by the world through recognition by UNESCO. The development of Bungo Batik began during the national event, Indonesia Fashion Craft in Makassar in 2002. The demand for Bungo Batik increases every year because it is supported by the policies of the Bungo Regency Regional Government. But on the one hand, the obstacle is precisely the craftsmen themselves who are not able to produce on a large scale. The partner in this activity is Batik Mulia which was established in 2021. The limited production capacity of Bungo batik is because the equipment used is still very simple, such as the use of waterglass in the manual batik dyeing process so that it is wasteful and immeasurable. In addition, partners also need training in management, entrepreneurship, branding strategies and the use of digital marketing. The method of implementing the activity begins with an agreement between the service team and partners to solve problems. The solution offered by the team to partners is the procurement of appropriate technological tools in the form of Roll Saving Water Glass machines and several trainings needed by partners. The success of this activity can be seen by several positive impacts from the savings or efficiency of the use of water glass in batik dyeing, increasing batik production, and improving partner skills in online promotion, creating marketing content and using digital marketing.